2013
DOI: 10.1007/s00701-013-1682-4
|View full text |Cite
|
Sign up to set email alerts
|

The clinical results of transcervical carotid artery stenting and frequency chosen as the approach route of carotid artery stenting in 1,067 consecutive cases

Abstract: CAS via a transcervical approach was safe and feasible, and its frequency chosen as an approach route was 0.9%. This procedure can be an alternative to transfemoral or transbrachial approaches when CAS via either of these approaches is too difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…An additional 9% were treated with a transbrachial approach. The remaining 10 cases (0.9%) could not be catheterized with either approach but were successful with a transcervical approach 7. The lesion was in the left carotid in 70% of the cases, again highlighting the challenge of catheterizing the left side.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional 9% were treated with a transbrachial approach. The remaining 10 cases (0.9%) could not be catheterized with either approach but were successful with a transcervical approach 7. The lesion was in the left carotid in 70% of the cases, again highlighting the challenge of catheterizing the left side.…”
Section: Discussionmentioning
confidence: 99%
“…Difficult catheter access can lead to lower rates of recanalization and ultimately poor clinical outcomes. Transcervical access has been a successful alternate strategy for carotid stenting7 and aneurysm coiling 8. In this study, direct percutaneous puncture and catheterization of the common carotid artery was instrumental in achieving rapid and successful revascularization in the case of acute stroke intervention.…”
Section: Discussionmentioning
confidence: 99%
“…CAS with the transbrachial approach has recently been reported [ 10 - 12 ]. Matsuda et al [ 13 ] reported that 9% (96/1,067) of CAS required the transbrachial approach. Conversely, there are a small number of reports regarding thrombectomy in acute ischemic stroke via the transbrachial approach [ 3 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transcervical access has been a successful alternate strategy for carotid stenting 10 and aneurysm coiling. 11…”
Section: Discussionmentioning
confidence: 99%